2019
DOI: 10.1002/app.47992
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible shape‐memory poly(vinyl chloride) with a tunable switching temperature via a plasticization effect

Abstract: Biocompatible shape‐memory poly(vinyl chloride) (PVC) with a tunable switching temperature (Ts) was fabricated via the incorporation of an environmentally friendly plasticizer of 1,2‐cyclohexane dicarboxylic acid diisononyl (DINCH). It was revealed that both of the shape‐memory effect (SME) and Ts were significantly influenced by the plasticization effect. With the addition of DINCH, the shape‐fixing ratio (Rf) showed a slight reduction, whereas the shape‐recovering ratio (Rr) was greatly enhanced, and Ts was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Limited by the human physiological environment, the switching temperature ( T s ) of shape-memory stents should be around body temperature for realizing body heat-triggering self-expansion or on-demand activation of shape transition. In principle, TSMPs are prepared by fabrication of the two-component structure containing switching and permanent domains. The switching component (SC) with a reversible thermal transition determines T s and controls the molecular chain movement with the temperature change, realizing fixation and activation of the temporary shape. Besides, the permanent component (PC) composed of either chemical or physical cross-links sets the permanent shape and ensures the recovery efficiency by restraining irreversible chain slippage.…”
Section: Introductionmentioning
confidence: 99%
“…Limited by the human physiological environment, the switching temperature ( T s ) of shape-memory stents should be around body temperature for realizing body heat-triggering self-expansion or on-demand activation of shape transition. In principle, TSMPs are prepared by fabrication of the two-component structure containing switching and permanent domains. The switching component (SC) with a reversible thermal transition determines T s and controls the molecular chain movement with the temperature change, realizing fixation and activation of the temporary shape. Besides, the permanent component (PC) composed of either chemical or physical cross-links sets the permanent shape and ensures the recovery efficiency by restraining irreversible chain slippage.…”
Section: Introductionmentioning
confidence: 99%
“…The EVM-GMA structure is similar to ethylene-vinyl acetate rubber (EVM), the only difference is that GMA polar groups increase its polarity. Both EVM-GMA and PVC have a certain shape memory performance 16,17 and they have great compatibility in theory due to their polarity. 18,19 PP Lizymol et al [20][21][22] found that PVC/EVA was a thermodynamic compatible system.…”
Section: Introductionmentioning
confidence: 99%